Validating The Croatian Version Of Five-Factor Personality Inventory (FFPI): Preliminary Results - Marušić, Iris (Array, 1997)
As a part of the project aimed at evaluating the most widely used personality questionnaires for the assessment of the five broad personality dimensions in Croatian population, this study attempted to collect some preliminary data relevant for the validation ofthe first translation of Five-Factor Personality Inventory (Hendriks, Hofstee, De Raad & Angleitner, 1995) into Croatian. Data were collected on a sample of 150 university students, and the instrument was administered along with the other two widely used personality instruments, NEO PI-R, assessing five-factor dimensions, and EPQ, assessing Eysenck's three dimensions. The results obtained suggest that FFPI scales have good reliability. Furthermore, the FFPI scales have relatively high correlation coefficients with the corresponding NEO PI-R and EPQ scales, thus showing good convergent validity. The only exception seems to be the poor correlation between the corresponding scales for the fifth, FFPI Intellect or NEO PI-R Openness factor, which is to be expected due to the conceptual differences that underlie the assessment of this factor in two questionnaires. In sum, the results with the first translated version of the FFPI provide evidence for its validity as a measure of five broad personality factors in Croatian population, provided some further refinement of the translation is made.